2020
DOI: 10.1111/imm.13229
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation by human IgG antibodies to galactose‐α‐1,3‐galactose

Abstract: Summary Some human antibodies may paradoxically inhibit complement activation on bacteria and enhance pathogen survival in humans. This property was also claimed for IgG antibodies reacting with terminal galactose‐α‐1,3‐galactose (Galα3Gal; IgG anti‐αGal), a naturally occurring and abundant antibody in human plasma that targets numerous different pathogens. To reinvestigate these effects, we used IgG anti‐αGal affinity isolated from a pool of normal human IgG and human hypogammaglobulinaemia serum as a complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…In general, phagocytosis of pneumococci requires opsonization by antibodies and complement fragments, especially fragments of C3. We recently reported that anti‐αGal bound on serotype 9V pneumococci activated the classical pathway of complement 38 . Here, we examine the opsonic effect of anti‐αGal bound on this pneumococcal serotype.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In general, phagocytosis of pneumococci requires opsonization by antibodies and complement fragments, especially fragments of C3. We recently reported that anti‐αGal bound on serotype 9V pneumococci activated the classical pathway of complement 38 . Here, we examine the opsonic effect of anti‐αGal bound on this pneumococcal serotype.…”
Section: Resultsmentioning
confidence: 97%
“…Structures of most capsular polysaccharides are reported, and none of these contains terminal Galα3Gal 48 . As antibody source, we used a well‐characterized and highly purified preparation of human anti‐αGal antibody of the IgG class 37,38 and examined its reactivity to 91 serotypes of S. pneumoniae by flow cytometry. A positive reaction was defined as more binding signal than the maximal signal observed with a control antibody of irrelevant specificity (IgG anti‐CD20 antibody).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jensen et al recently utilized hC3Nb1, hC3Nb2, and C1qNb75 to attribute the complement pathways elicited by these antibodies targeting the galactose-α-1,3-galactose carbohydrate. The authors reported that the anti-αGal antibodies elicit complement deposition by activating the classical pathway [ 121 ]. This basic research application is an example of how complement inhibitory nanobodies can be used to assign the contribution of the individual pathways to complement activation.…”
Section: Perspectivesmentioning
confidence: 99%